2010
DOI: 10.1007/s12291-010-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress in Type 2 Diabetes Mellitus and Follow-up Along with Vitamin E Supplementation

Abstract: Increased oxidative stress is a widely accepted participant in the development and progression of diabetes and its complications. The present study has been undertaken to evaluate oxidative stress in type 2 diabetes mellitus and effect of vitamin E supplementation on oxidative stress. In all 120 subjects were enrolled in the present study, 40 subjects are age and sex matched controls. Test group comprised of clinically diagnosed (n = 80) type 2 diabetic patients. Biochemical parameters like serum MDA, nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 16 publications
(13 reference statements)
3
24
0
Order By: Relevance
“…In this study the lipid peroxidation product, MDA measured as TBARS is significantly increased in type 2 diabetics than in controls. This finding is in accordance with findings of other studies as illustrated in Table: 5 [20], [21], [22], [23], [24], [25], [26], [27], [28]. The present study showed significantly increased ceruloplasmin levels in cases when compared to controls.…”
Section: Discussionsupporting
confidence: 93%
“…In this study the lipid peroxidation product, MDA measured as TBARS is significantly increased in type 2 diabetics than in controls. This finding is in accordance with findings of other studies as illustrated in Table: 5 [20], [21], [22], [23], [24], [25], [26], [27], [28]. The present study showed significantly increased ceruloplasmin levels in cases when compared to controls.…”
Section: Discussionsupporting
confidence: 93%
“…Shinde et al [22] demonstrated a reduction in oxidative stress and an improvement in antioxidant enzyme activity and vascular endothelial function in T2DM patients treated with anti-diabetic agents supplemented with vitamin E, as compared with patients treated only with glucose--lowering drugs. However, the pro-oxidative action of vitamin E, which depends on the dose, the duration of supplementation and the duration of diabetes, may alter the expected effect of supplementation [22]. In the present study, the participants' dietary intake of vitamin E and C were rather inadequate, therefore supplementation with these antioxidants would be probably favorable.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, vitamin E supplementation by T2DM patients can help to reduce the risk of developing cardiovascular disease by preventing the oxidation of low-density lipoproteins [15]. Shinde et al [22] demonstrated a reduction in oxidative stress and an improvement in antioxidant enzyme activity and vascular endothelial function in T2DM patients treated with anti-diabetic agents supplemented with vitamin E, as compared with patients treated only with glucose--lowering drugs. However, the pro-oxidative action of vitamin E, which depends on the dose, the duration of supplementation and the duration of diabetes, may alter the expected effect of supplementation [22].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this finding needs further investigation thus, up to now, many research have regarded the use of the antioxidant supplementation in type 2 diabetic subjects with conflicting results. In fact, several studies have demonstrated that in diabetic subjects vitamin E supplementation improves blood glucose levels [45], and oxidative status parameters [46]. As well as the combination of vitamin E and C reduced HbA1c and increased the activity of some antioxidant enzymes [47].…”
Section: Discussionmentioning
confidence: 99%